Pulse wave velocity – a new risk factor of target organ damage in hypertension - Pędzich-Placha, Ewa (Przewodnik Lekarza/Guide for GPs, 2008)
Hypertension is the leading cause of human cardiovascular morbidity and mortality, with a prevalence rate of 30% in the adult population. In consideration of the high general interest in cardiovascular diseases, the diagnostic improvement in assessing abnormalities in vascular wall structure and function by new techniques should be promptly put into practice, especially non-invasive ones. Guidelines from 2007 of the European Society of Hypertension (ESH) recommended measuring arterial stiffness in patients with arterial hypertension, suggesting a carotid-femoral pulse wave velocity over 12 m/s as an estimate of subclinical organ damage.